The Capsids of HIV-1 and HIV-2 Determine Immune Detection of the Viral cDNA by the Innate Sensor cGAS in Dendritic Cells - Lahaye, Xavier; Satoh, Takeshi; Gentili, Matteo; Cerboni, Silvia; Conrad, Cécile; Hurbain, Ilse; El Marjou, Ahmed; Lacabaratz, Christine; Lelièvre, Jean-Daniel; Manel, Nicolas (Immunity (Cambridge, Mass.), 2013)
HIV-2 is less pathogenic for humans than HIV-1 and might provide partial cross-protection from HIV-1-induced pathology. Although both viruses replicate in the T cells of infected patients, only HIV-2 replicates efficiently in dendritic cells (DCs) and activates innate immune pathways. How HIV is sensed in DC is unknown. Capsid-mutated HIV-2 revealed that sensing by the host requires viral cDNA synthesis, but not nuclear entry or genome integration. The HIV-1 capsid prevented viral cDNA sensing up to integration, allowing the virus to escape innate recognition. In contrast, DCs sensed capsid-mutated HIV-1 and enhanced stimulation of T cells in the absence of productive infection. Finally, we found that DC sensing of HIV-1 and HIV-2 required the DNA sensor cGAS. Thus, the HIV capsid is a determinant of innate sensing of the viral cDNA by cGAS in dendritic cells. This pathway might potentially be harnessed to develop effective vaccines against HIV-1. [Display omitted] •Human dendritic cells sense the cDNA of HIV-2 before integration•The HIV-1 capsid allows the virus to escape sensing of its cDNA by dendritic cells•Dendritic cells sense capsid-mutated HIV-1 without replication and stimulate T cells•The DNA sensor cGAS is essential in human dendritic cells for sensing HIV-1 and HIV-2